(untitled) (Journal of Hama University, 2024)
The research aimed to study the role of marketing vigilance in entrepreneurial orientation (Innovativeness, Proactiveness, Risk Taking) in Syriatel in Syrian Coast. Marketing vigilance is related to relationships, commercial activities, and marketing methods, as it focuses its attention on its front and back markets (customers, suppliers), It is a series of continuous and iterative processes through which organizations can monitor and analyze their marketing environment to obtain potential indicators of opportunities and threats that affect their survival. The researcher adopted the statistical method, and the preliminary data were collected through a questionnaire form as a tool for study, which was organized based on the researcher’s knowledge of published literature, questionnaire was distributed to a sample of research that represented by 65 consumers. In order to test hypotheses, the researcher unloaded a database using SPSS issue 23 and adopted on Alpha Crompbach to measure the stability of the meter. The researcher has provided a summary of the main result that there is Role of Marketing Vigilance in Entrepreneurial Orientation (Innovativeness, Proactiveness, Risk Taking ) in Syriatel in Syrian Coast.